Analysis of cardiac autonomic modulation in normotensive obese and eutrophic adults of Nepal - Yadav, Ram Lochan; Khadka, Rita; Agrawal, Kopila; Thakur, Dilip; Sharma, Deepak; Shah, Dev Kumar; Yadav, Prakash Kumar; Sapkota, Niraj Khatri; Paudel, Bishnu Hari; Islam, Md. Nazrul (International Journal of Research in Medical Sciences, 2016)
Background: Obese people have a higher prevalence of cardiovascular disease, though unknown mechanism, supposed to be due to autonomic dysfunction which is still in controversy. This study aimed to assess and compare heart rate variability (HRV) between normotensive obese and adults. Methods: The study was conducted on 30 normotensive obese adults (mean age 32.07±7.25 years) with BMI>30 and 29 age- and sex-matched normal weight controls (mean age 30.48±8.01 years) with BMI: 18-24 Kg/m2. Short-term HRV variables were assessed using standard protocol. The data were compared between the groups using Mann Whitney ‘U’ test. Results: In obese group, there was significant increase in the mean heart rate [79.17±8.80 Vs 71.48±8.41 beats/min, p=0.001], systolic blood pressure [121.20±9.89 Vs 113.24±11.07, mmHg, p=0.004] and diastolic blood pressure [84.97±7.87 Vs 74.83±10.31 mmHg, p=0.000]. The HRV parasympathetic indicators were less [RMSSD 28.75(16.72-38.35) Vs 41.55(30.6-56.75) ms, p=0.018, NN50 15.5(2-39) Vs 83.5(32.75-116.25), p=0.010], and sympathetic indicator LF/HF ratio [1.2(0.65-2.20) Vs 0.79(0.5-1.02), p=0.004] was more in obese group. Conclusions: Obese persons have increased sympathetic activity with a reduction in parasympathetic (vagal) tone indicating poor autonomic cardiac rhythm control. Moreover, the altered autonomic activity could be the reason for increased mean heart rate and blood pressures in normotensive obese persons.